2020
DOI: 10.1097/dss.0000000000002685
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Split-Body, Placebo-Controlled Trial to Evaluate the Efficacy and Safety of Poly-l-lactic Acid for the Treatment of Upper Knee Skin Laxity

Abstract: BACKGROUND Skin laxity of the upper knee and lower thigh is a common complaint among patients. OBJECTIVE This is a randomized, double-blinded, split-body, placebo-controlled study to evaluate the safety and efficacy of poly-l-lactic acid (PLLA) for treatment of upper knee skin laxity. MATERIALS AND METHODS Twenty female subjects between the ages of 30 and 65 years with upper knee laxity were enrolled. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Few minimally invasive options have been published like lipofilling, 115 microfocused ultrasound, 116 and more recently, collagen-stimulators such as CaHA 10 , 117 and PLLA. 98 , 118 , 119 …”
Section: Plla and Limbsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few minimally invasive options have been published like lipofilling, 115 microfocused ultrasound, 116 and more recently, collagen-stimulators such as CaHA 10 , 117 and PLLA. 98 , 118 , 119 …”
Section: Plla and Limbsmentioning
confidence: 99%
“…PLLA to correct skin laxity of the knees was assessed in three recent studies using different techniques and reported to lead to an improvement of skin laxity and a significant increase of skin thickness associated with a favorable safety profile ( Table 4 ). 98 , 118 , 119 They concerned few cases treated for this condition 98 , 118 although, interestingly a very recent randomized, double-blind, split-body placebo-controlled study was performed on 20 patients with mild-to-severe skin laxity, treated at the anterior upper knees. 119 The results showed a statistically significant improvement versus placebo on the primary endpoint, the PGAIS (Physician Global Aesthetic Improvement Scale) from 28 days to 168 days after 3 treatment sessions (1 vial/session; 16mL/vial).…”
Section: Plla and Limbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly-L–lactic acid (PLLA) in the form of Sculptra ® Aesthetic™ (Galderma Laboratories, L.P.) is used to increase the volume of depressed areas in the face and various body regions (eg, neck, decolletage, breasts, arms, hands, abdomen, thighs, knees, glutes). 1–7 The United States Food and Drug Administration approved PLLA in 2004 for the treatment of facial lipoatrophy and in 2009, for the indication of volume loss; 8 , 9 although it has been used in various medical applications for longer than three decades (eg, surgical stents and implants). 8 , 10 The mechanism of action of PLLA operates mainly through generating a foreign-body reaction.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 The resulting effect is a decrease in skin laxity and improvement in anatomical contours. 1 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%